2021
DOI: 10.1108/jima-04-2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Marketing advantages and sustainable competitiveness through branding for the supply chain of Islamic country

Abstract: Purpose Branding plays a vital role in the success of every organization and even industry. In Islamic countries, every organization must consider Sharia rules while strategy making. Nowadays, the supply chain is considered a major tool of branding and marketing. After an extensive literature review, it has been found that the studies that test the marketing advantages (MAs) and sustainable competitiveness through branding are scarce. The purpose of this study is to empirically examine the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…As per the study, motivating factors are environmental values. However, the results indicate egoistic value as a substantial determinant of attitude (Jiang et al , 2019; Shahbaz et al. , 2021).…”
Section: Discussion and Implicationmentioning
confidence: 70%
See 1 more Smart Citation
“…As per the study, motivating factors are environmental values. However, the results indicate egoistic value as a substantial determinant of attitude (Jiang et al , 2019; Shahbaz et al. , 2021).…”
Section: Discussion and Implicationmentioning
confidence: 70%
“…As per the study, motivating factors are environmental values. However, the results indicate egoistic value as a substantial determinant of attitude (Jiang et al, 2019;Shahbaz et al, 2021). Consequently, it is suggested that communication messages may include egoistic values to enhance a positive attitude.…”
Section: Implication For Managersmentioning
confidence: 81%
“…While evidence of and evaluation of brands and marketing in Islamic contexts exists (Georgiadou and Nickerson, 2021; Rhama, 2021; Shahbaz et al , 2021) and for those seeking Muslim tourists and customers (Chong et al , 2021; Sadom et al , 2021; Sulaiman et al , 2021), the present type of case is one not typically considered. For example, Alserhan (2010) suggests a framework for considering Islamic brands as “good deeds,” the performance of which is an important tenet in Islam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Enterprises should take careful consideration when choosing suppliers, such as taking note of the bullwhip effect in the clothing supply chain [12]. Managing the brand supply chain of garment enterprises is critical [13].…”
Section: Related Workmentioning
confidence: 99%